Plexin C1 deficiency permits synaptotagmin 7–mediated macrophage migration and enhances mammalian lung fibrosis. Issue 12 (8th September 2016) - Peng, Xueyan; Moore, Meagan; Mathur, Aditi; Zhou, Yang; Sun, Huanxing; Gan, Ye; Herazo‐Maya, Jose D.; Kaminski, Naftali; Hu, Xinyuan; Pan, Hongyi; Ryu, Changwan; Osafo‐Addo, Awo; et al.
ABSTRACT: Pulmonary fibrosis is a progressive and often fatal condition that is believed to be partially orchestrated by macrophages. Mechanisms that control migration of these cells into and within the lung remain undefined. We evaluated thecontributions of the semaphorinreceptor, plexinC1 (PLXNC1), andtheexocytic calcium sensor, synaptotagmin 7 (Syt7), in these processes. Weevaluated the role of PLXNC1 in macrophagemigration by using Boyden chambers and scratch tests, characterized its contribution to experimentally induced lung fibrosis inmice, and defined themechanism for our observations. Our findings reveal that relative to controlparticipants, patients with idiopathic pulmonary fibrosis demonstrate excessive monocyte migration and underexpression of PLXNC1 in the lungs and circulation, a finding that is recapitulated in the setting of scleroderma‐related interstitial lung disease. Relative to wild type, PLXNC1 ‐/‐ mouse macrophages are excessively migratory, and PLXNC1 ‐/‐ mice show exacerbated collagen accumulation in response to either inhaled bleomycin or inducible lung targeted TGF‐β1 overexpression. These findings are ameliorated by replacement of PLXNC1 on bone marrow–derived cells or by genetic deletion of Syt7. These data demonstrate the previously unrecognized observation that PLXNC1 deficiency permits Syt7‐mediated macrophage migration and enhances mammalian lung fibrosis.—Peng, X., Moore, M., Mathur, A., Zhou, Y., Sun, H., Gan, Y., Herazo‐Maya, J. D., Kaminski, N., Hu, X., Pan, H., Ryu, C., Osafo‐Addo, A., Homer, R. J., Feghali‐Bostwick, C., Fares, W.H., Gulati, M., Hu, B., Lee, C.‐G., Elias, J. A., Herzog, E. L. Plexin C1 deficiency permits synaptotagmin 7–mediated macrophage migration and enhances mammalian lung fibrosis. FASEB J. 30, 4056–4070 (2016). www.fasebj.org